Is implementation of the 2013 Australian treatment guidelines for posttraumatic stress disorder cost-effective compared to current practice? A cost-utility analysis using QALYs and DALYs. (April 2015) - Mihalopoulos, Cathrine; Magnus, Anne; Lal, Anita; Dell, Lisa; Forbes, David; Phelps, Andrea
Objective: To assess, from a health sector perspective, the incremental cost-effectiveness of three treatment recommendations in the most recent Australian Clinical Practice Guidelines for posttraumatic stress disorder (PTSD). The interventions assessed are trauma-focused cognitive behavioural therapy (TF-CBT) and selective serotonin reuptake inhibitors (SSRIs) for the treatment of PTSD in adults and TF-CBT in children, compared to current practice in Australia. Method: Economic modelling, using existing databases and published information, was used to assess cost-effectiveness. A cost-utility framework using both quality-adjusted life-years (QALYs) gained and disability-adjusted life-years (DALYs) averted was used. Costs were tracked for the duration of the respective interventions and applied to the estimated 12 months prevalent cases of PTSD in the Australian population of 2012. Simulation modelling was used to provide 95% uncertainty around the incremental cost-effectiveness ratios. Consideration was also given to factors not considered in the quantitative analysis but could determine the likely uptake of the proposed intervention guidelines. Results: TF-CBT is highly cost-effective compared to current practice at 19, 000/QALY, 16, 000/DALY in adults and 8900/QALY, 8000/DALY in children. In adults, 100% of uncertainty iterations fell beneath the 50, 000/QALY or DALY value-for-money threshold. Using SSRIs in people already on medications is cost-effective at 200/QALY, but has considerable uncertainty around the costs and benefits. While there is a 13% chance of health loss there is a 27% chance of the intervention dominating current practice by both saving dollars and improving health in adults. Conclusion: The three Guideline recommended interventions evaluated in this study are likely to have a positive impact on the economic efficiency of the treatment of PTSD if adopted in full. While there are gaps in the evidence base, policy-makers can have considerable confidence that the recommendations assessed in the current study are likely to improve the efficiency of the mental health care sector.